Penegakkan Etik Notaris Di Wilayah Hukum Kota Bandung - Jahir, Faidh Fauzan (Pemuliaan Hukum, 2023)
Abstract Enforcement of notary professional ethics is an important aspect in maintaining the integrity and professionalism of notaries. There are a number of cases of violations of the code of ethics by notaries that have come into the public spotlight. This indicates that there are weaknesses in the ethics enforcement mechanism at the MPD. This research uses empirical juridical methods that focus on primary data. The research objectives regarding enforcement of the notary code of ethics in the Regional Supervisory Council (MPD) of Bandung City include several important aspects, including: Understanding the Role of the MPD, Analyzing the Effectiveness of Supervision, and Providing Recommendations. Based on the research results, ethical enforcement that occurs at the Regional Supervisory Council when there is a report of a violation of the professional rules or duties of a Notary Public can submit a report in writing. The report will be followed up immediately, starting from the Chairman of the MPD who will form an Examining Council in accordance. However, the Examining Council has no authority to impose sanctions on the reported Notary. Regional Audit Council and the Central Audit Council have the authority to investigate and decide on reports received. The obstacle in enforcing notary ethics is that MPW does not follow up on MPD recommendations, causing the law enforcement process regarding public reports to be unresolved or there is no decision. There are efforts including: Improving the Reporting and Follow-up Process, Coordination with the MPD and Authorities, Strengthening the Authority and Capacity of the MPD, Counseling and Education for Notaries and the Community, and mentoring and periodic evaluations. The suggestion is to optimize the use of information technology by building a digital-based monitoring system. Keywords : Ethics; Obstacles; Regional Supervisory Council; Effort. Abstrak Penegakan etika profesi notaris merupakan aspek penting dalam menjaga integritas dan profesionalisme notaris. Terdapat sejumlah kasus pelanggaran kode etik oleh notaris yang menjadi sorotan publik. Hal ini mengindikasikan adanya kelemahan dalam mekanisme penegakan etik di MPD. Penelitian ini menggunakan metode yuridis empiris yang berfokus pada data primer. Tujuan penelitian mengenai penegakan kode etik notaris di Majelis Pengawas Daerah (MPD) Kota Bandung meliputi beberapa aspek penting, antara lain: Memahami Peran MPD, Menganalisis Efektivitas Pengawasan, dan Memberikan Rekomendasi. Berdasarkan hasil penelitian, penegakan etik yang terjadi di Majelis Pengawas Daerah ketika terjadi laporan pelanggaran terhadap tata tertib profesi atau tugas Notaris, dapat menyampaikan laporan seacara tertulis. Laporan segera ditindaklanjuti, dimulai dari Ketua MPD yang akan membentuk Majelis Pemeriksa. Namun, Majelis Pemeriksa tidak berwenang memberikan sanksi terhadap terlapor Notaris. Majelis Pemeriksa Wilayah dan Majelis Pemeriksa Pusat berwenang menyelidiki dan memutus laporan yang diterima. Kendala dalam penegakan etik notaris adalah tidak ditindaklanjutinya rekomendasi MPD oleh MPW, menyebabkan proses penegakan hukum terhadap laporan Masyarakat menjadi tidak terselesaikan atau tidak adanya putusan. Terdapat upaya diantaranya: Meningkatkan Proses Pelaporan dan Tindak Lanjut, Koordinasi dengan MPD dan Pihak Berwajib, Penguatan Wewenang dan Kapasitas MPD, Penyuluhan dan Edukasi kepada Notaris dan Masyarakat, dan mentoring serta evaluasi berkala. Saran yakni pengoptimalkan penggunaan teknologi informasi dengan membangun sistem pengawasan berbasis digital. Kata Kunci : Etik; Kendala; Majelis Pengawas Daerah; Upaya.